English as a Medium of Instruction: Students' Strategies - Soruç, Adem; Griffiths, Carol (ELT journal, 2018)
Although English-medium instruction (EMI) is now widely spread throughout the world, there is surprisingly little research into the challenges students face as they try to learn subject matter by means of a non-native language, or how learners attempt to address these challenges. The study reported in this article employed a qualitative approach, using video-recording, an open-ended questionnaire, and stimulated-recall interviews to investigate the difficulties faced by students working in International Relations and Psychology classes in a Turkish university. The students were also asked to identify the strategies they used in an attempt to cope with these difficulties. The students were indeed able to list a number of difficulties, but numerous strategies were also suggested to deal with the problems they faced. Implications are suggested for student support and teacher training, as well as suggestions for ongoing research.